GOUT OUTCOMES. A REVIEW OF LITERATURE. PART 1. GOUT: EPIDEMIOLOGY, RISK FACTORS, COURSE OF THE DISEASE WITH THE DEVELOPMENT OF CHRONIC TOPHUS FORM - Igor Sergeyevich Denisov; M S Eliseev; V G Barskova (Научно-практическая ревматология)
The paper gives data on the epidemiology and risk factors of gout. It considers remission and transition of the disease to its chronic form as possible outcomes of the disease and presents data on its progression and the impact of drugtherapy on the course of the disease.